Pengaruh Aktivasi Dalam Penurunan Kandungan (Pb) Dalam Air Laut Menggunakan Tanah Lempung Sebagai Penukar Ion - Hafiz Hafiz; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bengkalis has a characteristic red soil water that people use other alternatives such as the use of rain water as drinking water, seawater however Bengkalis potentially be processed into clean water. One alternative treatment of sea water into fresh water is to use ion exchange method. This study uses an ion exchange method which utilizes clay Kulim. As well as ion exchange column used 2 inch diameter and a height of 1.2 meters. The medium used is activated clay and sea water Bengkalis Island. Variation used is acid solution HCl, HNO3, and H2SO4 with each solution concentration 2M and clay without activation as a control. Used detention time is 180 minutes, while the clay size -10+15 mesh. From the results, the highest efficiency in H2SO4 activated clay with an efficiency of 95.2% Pb concentration of 1.201 mg/L to 0.058 mg/L. When in comparison with clean water quality standard Pb concentration in sea water not meet quality standards. Then calculated the value of the clay CEC and CEC highest value obtained is 124.16 meq/g on activated clay H2SO4 These results indicate that the ion exchange method using activated clays are capable of removing Pb and Ca concentrations in seawater.Keywords: Acid Solution, Ion Exchange, Kulim Activated Clay Soil, Sea Water of Bengkalis